A Legal Analysis of the Regulation of Unfair Commercial Practices Under the Consumer Protection Act 68 of 2008 - Magau, Phemelo (University of Pretoria, 2024)
Mini Dissertation (LLM (Mercantile Law))--University of Pretoria, 2023.